Bacillus subtilis spores displaying Toxoplasma gondii GRA12 induce immunity against acute toxoplasmosis - Sun, Hong-chao; Yuan, Xiu-fang; Zhou, Wei; Zhou, Zhi-jin; Su, Fei; Fu, Yuan; Hao, Li-li; Liu, Xin; Zhou, Xin; Ye, Shi-yi; Xu, Li-hua; Yu, Bin; et al. (Frontiers in Immunology, 2025)
BackgroundToxoplasma gondii (T. gondii) is a widely prevalent intracellular parasite that infects almost all warm-blooded animals and causes serious public health problems. The drugs currently used to treat toxoplasmosis have the disadvantage of being toxic and prone to the development of resistance, and the only licensed vaccine entails a risk of virulence restoration. The development of a safe and effective vaccine against T. gondii is urgently needed. Bacillus subtilis (B. subtilis) has been used as a potential vaccine expression vector for the treatment and prevention of various diseases. T. gondii GRA12 is a key virulence factor that resists host innate immunity and exhibits good antigenicity with several excellent B and T cell epitopes.MethodsA recombinant spore named rBS-GRA12 was constructed by fusing the T. gondii GRA12 protein to the B. subtilis coat protein B (CotB). rBS-GRA12 spores were identified by PCR, western blotting, immunofluorescence assays, amylase activity, and ultrastructural analysis. Immunological experiments were then conducted to assess the immunoprotective effects of rBS-GRA12. Groups of mice immunized with rBS-GRA12 (106, 108, or 1010 colony-forming units), GRA12 protein emulsified with Freund’s adjuvant (FA+GRA12), Freund’s adjuvant alone (FA), phosphate buffered saline (PBS), or wild-type B. subtilis spores (WT). Splenocyte proliferation, antibodies, and cytokine expression levels were used to assess immune responses induced by the immunizations. All groups were inoculated with T. gondii RH strain, and survival times and parasite loads in tissues were used to assess protective effects against T. gondii infection.ResultsAmylase activity assays confirmed the generation of recombinant B. subtilis. PCR, western blotting and immunofluorescence assays confirmed that the rBS-GRA12 spores expressed GRA12. Observation of rBS-GRA12 spores via transmission and scanning electron microscopy indicated that GRA12 expression had no effect on spore morphology or structure. Splenocyte proliferation was significantly greater in all three rBS-GRA12 groups than in the FA+GRA12 group, and IgG and IgG2a subclass titers were higher. Substantial production of interferon gamma (IFN-γ), interleukin (IL)-12, and an increase in IL-4 production were evident in the rBS-GRA12-108 group. Secretory sIgA levels were significantly elevated in all three rBS-GRA12 groups than in the FA+GRA12 group and the control groups. Brain and liver tissues parasite loads were significantly lower in the three rBS-GRA12 groups than in any other group. Compared to all other groups, mice in the three rBS-GRA12 groups exhibited longer survival times when challenged with acute T. gondii infection.ConclusionMice immunized with rBS-GRA12 exhibited higher levels of cellular, humoral, and mucosal immune responses than control mice. These results provide a new perspective for the development of T. gondii vaccines.